Active commuting to school: Barriers and facilities identified in the speeches of children in a public school system - Olga Maria da Silva Bezerra Cavalcanti; Joel Siqueira Junior; Francisco Timbó de Paiva Neto; Cassiano Ricardo Rech (Journal of Physical Education (Maringá), 2025)
Objective: To identify barriers and facilitators for active commuting to school, based on the discourses of children enrolled in the public school system of a southern Brazilian capital. Methods: This is a descriptive, qualitative study conducted in Florianópolis, SC, between May and June 2023. Sociodemographic questionnaires and focus groups were used to explore the children's accounts of their home-to-school commute. Data analysis was performed using descriptive statistics and discourse analysis. Results: The study included 24 students (58.3% girls) aged 9 to 12, all in the fifth grade of elementary school. Four categories of barriers emerged from the children's discourses: lack of infrastructure for walking and cycling, absence of public transportation, poor neighborhood aesthetics, and lack of safety. Among the facilitators, social interaction, health benefits, and the presence of social amenities stood out. Conclusion: Barriers and facilitators on the home-to-school route directly impact the active commuting of students in Florianópolis's public school system. Improvements to neighborhood environments may be promising strategies for increasing active commuting among schoolchildren.